Academic Research Underlying Industrial Innovations: Sources, Characteristics, and Financing - Mansfield, Edwin (The Review of Economics and Statistics, 1995)
There has been no systematic study of the characteristics of the universities and academic researchers that seem to have contributed most to industrial innovation. Nor do we know how such academic research has been funded. This paper, based on data obtained from 66 firms in seven major manufacturing industries and from over 200 academic researchers, sheds new light on the sources, characteristics, and financing of academic research underlying industrial innovation. The findings should be of interest to economists concerned with technological change and to policy makers attempting to increase the economic payoff from the nation's academic research.